Unlocking the Poverty-Alleviating Potential of Zakat: A Case Study of the Sentra Ternak Mandiri, Ummul Quro Zakat Managgement Institution - Kurniawati, Sarah (Sharia and Law Faculty of Sunan Kalijaga Islamic State University Yogyakarta, 2023)
Abstract: The purpose of Islamic economic instruments (zakat, infaq, sadaqah) is not achieved, because the poverty rate tends to increase. Poverty alleviation through sharia instruments will not succeed if it is done in a consumptive manner. Zakat must begin to be seen as an important instrument in the Islamic economy that is managed productively and sustainably. This article aims to analyze the utilization of zakat for productive businesses at Amil Zakat Institution Ummul Quro Jombang Regency, namely with the Mandiri Livestock Center program. This article is a field research whose data is managed qualitatively. Data were obtained through interviews, observations, and documentation on the Sentra Ternak Mandiri program run by Lembaga Amil Zakat Ummul Quro Jombang. Through descriptive analysis, this study found that zakat management in this institution succeeded in managing zakat funds by ensuring an increase in mustahik income through independent livestock business productivity. The success of zakat utilization is thanks to mentoring, counseling and evaluation of zakat fund management. The management of the Independent Livestock Center is in accordance with the objectives of zakat in the philosophy of Islamic law and the Minister of Religious Affairs Regulation Number 52 of 2014. This article argues that poverty alleviation through Islamic economic instruments will not succeed if the management only stops at distribution. Furthermore, to increase the role of Islamic economy in alleviating poverty, amil zakat needs to be more creative in creating productive zakat management assistance programs.The implication of this article shows that assistance, supervision, and evaluation of the productivity of zakat management need to be carried out by national and private amil zakat.Abstrak: Tujuan instrumen ekonomi Islam (zakat, infak, sedekah) tidak tercapai, karena tingkat kemiskinan cenderung bertambah. Pengentasan kemiskinan melalui instrumen syariah tidak akan berhasil jika dilakukan dengan cara konsumtif. Zakat harus mulai dipandang sebagai instrumen penting dalam ekonomi Islam yang dikelola secara produktif dan berkelanjutan. Artikel ini bertujuan untuk menganalisis pendayagunaan zakat untuk usaha produktif di Lembaga Amil Zakat Ummul Quro Kabupaten Jombang yaitu dengan program Sentra Ternak Mandiri. Artikel ini merupakan penelitian lapangan yang datanya dikelola secara kualitatif. Data diperoleh melalui wawancara, observasi, dan dokumentasi pada program Sentra Ternak Mandiri yang dijalankan oleh Lembaga Amil Zakat Ummul Quro Jombang. Melalui analisis deskriptif, penelitian ini menemukan bahwa pengelolaan zakat pada lembaga ini berhasil mengelola dana zakat dengan memastikan peningkatan pendapatan mustahik melalui produktifitas usaha ternak mandiri. Keberhasilan pendayagunaan zakat ini berkat pendampingan, penyuluhan hingga evaluasi pengelolaan dana zakat. Pengelolaan Sentra Ternak Mandiri sesuai dengan tujuan zakat dalam filsafat hukum Islam maupun Peraturan Menteri Agama Nomor 52 Tahun 2014. Artikel ini berargumen bahwa pengentasan kemiskinan melalui instrumen ekonomi Islam tidak akan berhasil jika pengelolaannya hanya berhenti pada distribusi. Lebih jauh, untuk meningkatkan peran ekonomi Islam dalam mengentaskan kemiskinan, amil zakat perlu lebih kreatif membat program pendampingan pengelolaan zakat secara produktif. Implikasi artikel ini menunjukkan bahwa pendampingan, penyulhan, dan evaluasi produktifitas pengelolaan zakat perlu dilakukan oleh amil zakat nasional maupun swasta.